Assessment of copper and zinc contamination in paddy soils and grains from Kemuning and Kelaweh, Kelantan: implications for sustainability and planetary health - Yap, C. K.; Al-Mutairi, K. A. (Corvinus University of Budapest, 2025)
This study aimed to investigated the concentrations of copper (Cu) and zinc (Zn) in paddy tissues and associated topsoils from Kemuning and Kelaweh, Kelantan. It assessed the potential ecological and health risks linked to metal accumulation. The results revealed significantly (P< 0.05) higher Cu and Zn concentrations in Kelaweh than Kemuning, particularly in the outlet zones, where metal accumulation was the most pronounced. The contamination factor and ecological risk index indicated that Kelaweh has a greater contamination potential, with Cu target hazard quotient (THQ) values exceeding the safe threshold for adults, suggesting a potential health risk. Zn levels, though elevated, did not pose an immediate health concern, as THQ values remained below risk thresholds. These findings highlighted the need for sustainable agricultural practices, improved water management, and continuous monitoring to ensure food safety and protect planetary health. The study emphasized the critical link between soil health, food security, and ecosystem sustainability in the context of rising environmental pressures. By understanding the current levels of metal contamination and the associated risks, policymakers and farmers can implement targeted interventions to ensure that paddy cultivation remains sustainable and contributes positively to planetary health.